Utilizing student response systems in a high school mathematics class - Hammil, Lynette (My University, 2011)
An important aspect of teaching is to engage students in the learning process. Evidence has shown that the use of technology to increase engagement and participation of students in the classroom is important. The use of technology in a high school mathematics classroom to engage students was investigated in this study. The purpose was to determine if the use of student response systems or clickers in the classroom engaged more students than a classroom not using the technology. The second part of this study was to investigate whether the use of this technology increased student test scores. This study took place in a high school mathematics class during the 2010-2011 school year, in South Central Wisconsin. The study involved data gathered from classroom observations, student surveys, student interviews, quiz and test results, and the teacher's journal. The student surveys and interviews were overwhelmingly positive in using clickers to increase engagement during the class period. The students agreed that using clickers made the math lectures more interesting. The teacher's journal and classroom observations provided insight into the use of the clickers to promote discussion, instant feedback, and effectively implementing clickers in the lecture. The quiz and test results were inconclusive. There were too many factors to consider when looking at the comparison results, such as the students? overall math skills. This study is important to teachers and administration who are investigating ways to incorporate technology into the classroom. The benefit that the clicker technology offers in student engagement and participation should be considered as a supplement to the classroom.
This file was last viewed in Adobe Reader 10.0.1
Keywords: Student response systems; Mathematics--Study and teaching (Secondary); Educational tests and measurements